(untitled) (Journal of actual problems of jurisprudence, 2018)
This article examines one of the basic and scientific development problems requiring international legal protection of the environment from the adverse effects of space activities. Since the issue in question is complex and mass lesion in the article the main sources of international legal protection of the environment from the adverse effects of space activities. Key words: environment, the source, negative effects, space activities.